2000
DOI: 10.1002/1097-0029(20001101)51:3<280::aid-jemt7>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Integrins as receptors for laminins

Abstract: Laminins are a family of trimeric glycoproteins present in the extracellular matrix and the major constituents of basement membranes. Integrins are αβ transmembrane receptors that play critical roles in both cell‐matrix and cell‐cell adhesion. Several members of the integrin family, including α1β1, α2β1, α3β1, α6β1 , α7β1 and α6β4 heterodimers serve as laminin receptors on a variety of cell types. This review summarizes recent advances in understanding the involvement of individual integrins in cell interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
214
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(223 citation statements)
references
References 269 publications
(259 reference statements)
7
214
1
1
Order By: Relevance
“…In our study, rLaminin-521 which was the basement membrane component acted as a scaffold to maintain the cell adhesion [47,48] were used in an attempt to improve cell adhesion factor on the dish in 2D culture. This component was capable of adhering intestinal cells on the dish.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, rLaminin-521 which was the basement membrane component acted as a scaffold to maintain the cell adhesion [47,48] were used in an attempt to improve cell adhesion factor on the dish in 2D culture. This component was capable of adhering intestinal cells on the dish.…”
Section: Discussionmentioning
confidence: 99%
“…The subunits share homology in the cytoplasmic tail, with tyrosine residues able to bind intracellular proteins containing a phosphotyrosine binding domain. The binding of integrins to ECM leads to a conformation change and a signal is activated at the contact site via cytoskeleton proteins such as actin and intermediate filament proteins [20]. The cytoplasmic domain of integrins binds directly or indirectly to several proteins, including talin, vinculin, filamin, paxillin, and tensin [21,22].…”
Section: Integrinmentioning
confidence: 99%
“…3,4 The a6-subfamily of integrins are key mediators of cellular interactions with their environment, forming heterodimers with b4 (associated with stable hemidesmosomes and cell-cell adherence) or b1 (involved in the formation of dynamic focal contacts for cell locomotion). In addition, a6 (CD49f) and b1 (CD29) integrins have recently been shown to be stem cell markers being highly expressed on mammary epithelial stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Both a6b1 and a6b4 integrins are thought to bind primarily to laminin, specifically the elastasegenerated E8 fragment of the laminin a1 chain. 4 Tashiro et al 23 identified the peptide sequence IKVAV located within the E8 region that promoted cell adhesion, spreading and neurite outgrowth. SIKVAV mediated urokinase-type plasminogen activator (uPa) expression in macrophages 24 and mast cell adherence to a SIKVAV containing peptide 25 can both be blocked using monoclonal antibodies directed against the a6 integrin subunit.…”
Section: Introductionmentioning
confidence: 99%